Composting of halophyte Phragmites australis following phytoaccumulation of chloride from a cement kiln dust (CKD)-contaminated landfill. (15th March 2019) - Yun, K.; Rutter, A.; Zeeb, B.A.
Highlights: Composting significantly reduced P. australis biomass by 87 ± 6% and 89 ± 8% in field. Rinsing with water is an important step in removing chloride from plant material. Harvesting after salt phytoextraction remediates site and removes invasive species. Abstract: Cement kiln dust (CKD) is a highly saline waste by-product of the cement manufacturing process. Plant and aquatic communities may be negatively impacted by elevated concentrations of chloride in and around CKD landfills. Phytoextraction is currently being employed to remediate an area adjacent to a CKD landfill [Cl − ]soil = 4730 ± 5980 μg/g; n = 100) in Bath, ON using the resident accumulator halophyte, Phragmites australis (haplotype M). In this paper, composting is explored as a sustainable disposal option for dealing with salt-contaminated plant waste. After one growing season (May – September 2015), shoots of P. australis were harvested and placed in laboratory tumbling composters for 12 months. The plant biomass (3720 ± 150 g) was reduced by 28 ± 6%, and with thorough rinsing, a 49 ± 18% reduction of chloride was achievable within the same time period. Composting was repeated outdoors at the field site in both closed tumbling composters, and open compost piles. In both cases, superior chloride concentration reductions of 87 ± 6% and 89 ± 8%, respectively were achieved. This is the first study to demonstrate that composting of harvested biomass following phytoextraction of salt can be used to sustainably manage plant waste.